Zoom for dummies - Simon, Phil 1972- (Wiley, 2020)
Unlock the full potential of Zoom'with this straightforward'resource' Zoom'For'Dummies'shows readers how to stay connected to their friends, family, colleagues, and peers with this explosively popular'communication platform. Written by'business professional Phil Simon,'Zoom'For'Dummies'allows you to take full advantage of Zoom's multi-faceted feature set, including:'' The "Meetings" feature''> Webinar capabilities''> Instant messaging functionality'> Zoom's 'Channel' features'> > Zoom'>For'Dummies>'goes beyond video'conferencing and'unlocks the full power of this'service. You'll be able to'connect with people around the globe,'record and replay video,'share your screen with others,'and use Zoom on your desktop, laptop, tablet, and mobile device.'</ The book shows you how to follow best practices when it comes to Zoom's'enhanced'security features, as well as how to keep Zoom'up to date. Written in the'friendly'style the'For Dummies'>series is famous for,'Zoom'For'Dummies'>is perfect for anyone who uses Zoom for school, work, business, or personal reasons.'<